Eksegesis Penghukuman Allah Bagi Ciptaan - Chia, Philip Suciadi (STT Injili Indonesia Medan, 2021)
Abstract: There are some similarities and differences between the punishments that the Serpent and Adam received. Either in the reason why it was punished, or the form of punishment received. The common reason for their punishment is that they have similar active actions, but the difference is that the serpent has done (14a) while Adam has listened (17a). The form of punishment received by the serpent was